Analysis of the epidemiological profile of men treated with acute pancreatitis in urgent regime in north of Minas - Teixeira Teles Gonçalves, Jaqueline; Teles Gonçalves, Camila; Araújo Resende, Morgana; Rocha Parada, Fernando; Fernando Gouvea Jabbur, Iann; José Faria, Plínio; Ferreira Santana, Renata; Andrade de Prince, Karina (Revista Unimontes Científica, 2020)
ANÁLISE DO PERFIL EPIDEMIOLÓGICO E MORBIMORTALIDADE DE HOMENS ATENDIDOS COM PANCREATITE AGUDA EM REGIME DE URGÊNCIA NO NORTE DE MINAS Abstract: Introduction: Acute pancreatitis is one of the most common inflammatory processes of the gastrointestinal tract, making a major impact on patients' lives. Its main causes are gallbladder stones and alcohol. Objectives: to analyze the epidemiological and morbimortality profile of acute pancreatitis in men treated as an emergency in the North of Minas Gerais. Methodology: epidemiological, descriptive and quantitative research in patients with acute pancreatitis in men treated as an emergency in the health services of the North of Minas Gerais during the period from 2008 to 2017. Data were obtained from the Hospital Information System of the SUS. Results: There was an increase in the number of hospitalizations between 2009 and 2016, with a higher frequency between 30 and 39 years (n = 683) and brown (n = 1078). The highest number of deaths between 30 and 39 years (n = 33). There were more hospitalizations in the public sector (n = 942) than in the private sector (n = 891). Spending was higher in the private sector. Regarding the average length of stay, there was an overall average of 6.4 days in the public sector and 5.6 days in the private sector. The mortality rate remains approximately constant in the age groups from 20 to 29 years (3.93%), 30 to 39 years (4.8%) and 40 to 49 years (5.3%). Conclusion: AP is a serious disease that, if not promptly diagnosed and treated, has a tragic outcome. In this context, studies like this are important to serve as a basis for health authorities in decision-making and make the best resources used. Resumo: Introdução: A pancreatite aguda é um dos processos inflamatórios mais comuns do trato gastrointestinal, constituindo um grande impacto na vida dos pacientes. Suas principais causas são cálculo biliar e abuso de álcool. Objetivos: analisar o perfil epidemiológico e de morbimortalidade da pancreatite aguda em homens atendidos em caráter de urgência no Norte de Minas. Metodologia: investigação de caráter epidemiológico, descritivo, e quantitativo em portadores de pancreatite aguda em homens atendidos em caráter de urgência nos serviços de saúde do Norte de Minas, durante o período de 2008 a 2017. Os dados foram obtidos do Sistema de Informações Hospitalares do SUS. Resultados: Ocorreu um aumento do número de internações entre 2009 a 2016 com maior frequência entre 30 e 39 anos (n=683) e na raça parda (n=1078). Maior número de óbitos entre 30 e 39 anos (n=33). Ocorreram mais internações no setor público (n=942), do que no privado (n=891). Os gastos foram maiores no setor privado. Acerca da média de permanência, houve média geral de 6,4 dias no setor público e 5,6 dias no setor privado. A taxa de mortalidade se mantém aproximadamente constante nas faixas etárias de 20 a 29 anos (3,93%), 30 a 39 anos (4,8%) e 40 a 49 anos (5,3%). Conclusão: A PA é uma doença grave que, se não for prontamente diagnosticada e tratada, possui um desfecho trágico. Nesse contexto, estudos como esse são importantes para servir como base para as autoridades de saúde na tomada de decisões e tornar os recursos melhores aproveitados.